Corrosion assessment on reinforced concrete and its service life prediction - Syed Mohamad, Syed Burhanuddin Hilmi (2005)
Deterioration of structural concrete may be caused either by chemical or physical effects. Corrosion of embedded steel is a major cause of deterioration of concrete structures at the present time. This lead to structural weakening due to loss of steel cross-section, surface staining, cracking or spalling and delamination of concrete and then gradually reduces the service life of the reinforced concrete structures. The most biggest problem is concerned with the structural integrity and safety of reinforced concrete structures by reducing the load carrying capacity. This project was to assess the degree of corrosion on reinforced concrete structure and estimating the residual service life. It was conducted based on electrochemical methods. These methods include galvanostatic pulse method and linear polarization method. A Non-Destructive Test techniques called GalvaPulse was used in this study. These equipments allow us to determine the degree of corrosion, rate of corrosion and interpret the result in corrosion mapping. From the results, assessment on the validation of corrosion in short and long terms by using predictive models are discussed.